Clinicohematological profile of acute febrile illness: Experiences in a hospital catering to semi-urban pediatric population of Delhi - Safia, Rana; Tabish, Mohd; Zeeba, Jairajpuri S; Sujata, Jetley; Shaan, Khetrapal; Kumar, Chandra Mohan (Indian Journal of Child Health, 2019)
Background: Among the pediatric age group, acute febrile illness (AFI) is a major cause of hospital admission, causing morbidity and death among children worldwide. Dengue, typhoid, malaria, and chikungunya fever are some of the common causes in Indian clinical settings. Objective: The objective of the study was to analyze the spectrum of AFI in pediatric population along with the evaluation of hematological parameters and to determine the specific causes and also the prognostic implications of these parameters. Materials and Methods: Patients from the pediatric outpatient department presenting with AFI formed the subjects of this study. Hematological profiles and biochemical investigations of atrial fibrillation cases were carried out and correlated. Statistical analysis was done. Results: In case of malaria and typhoid fever, leukopenia was statistically significant. Significant difference (p